Management of hemodynamically stable wide QRS complex tachycardia in patients with implantable cardioverter defibrillators - Regoli, François D.; Cattaneo, Mattia; Kola, Florenc; Thartori, Albana; Bytyci, Hekuran; Saccarello, Luca; Amoruso, Marco; Di Valentino, Marcello; Menafoglio, Andrea (Frontiers in Cardiovascular Medicine, 2023)
Management of hemodynamically stable, incessant wide QRS complex tachycardia (WCT) in patients who already have an implantable cardioverter defibrillator (ICD) is challenging. First-line treatment is performed by medical staff who have no knowledge on programmed ICD therapy settings and there is always some concern for unexpected ICD shock. In these patients, a structured approach is necessary from presentation to therapy. The present review provides a systematic approach in four distinct phases to guide any physician involved in the management of these patients: PHASE I: assessment of hemodynamic status and use of the magnet to temporarily suspend ICD therapies, especially shocks; identification of possible arrhythmia triggers; risk stratification in case of electrical storm (ES). PHASE II: The preparation phase includes reversal of potential arrhythmia “triggers”, mild patient sedation, and patient monitoring for therapy delivery. Based on resource availability and competences, the most adequate therapeutic approach is chosen. This choice depends on whether a device specialist is readily available or not. In the case of ES in a “high-risk” patient an accelerated patient management protocol is advocated, which considers urgent ventricular tachycardia transcatheter ablation with or without mechanical cardiocirculatory support. PHASE III: Therapeutic phase is based on the use of intravenous anti-arrhythmic drugs mostly indicated in this clinical context are presented. Device interrogation is very important in this phase when sustained monomorphic VT diagnosis is confirmed, then ICD ATP algorithms, based on underlying VT cycle length, are proposed. In high-risk patients with intractable ES, intensive patient management considers MCS and transcatheter ablation. PHASE IV: The patient is hospitalized for further diagnostics and management aimed at preventing arrhythmia recurrences.